(untitled) (Diametros, 2015)
Solidarity is analysed in contradistinction from two adjacent concepts - justice and sympathy. It is argued that unlike the other two, it is essentially local (rather than universal), partial (rather than impartial) and reflective (an emotion mediated by belief and ideology, interest and common cause). Although not to be confused with justice, solidarity is presented as underlying any contract-based system of justice, since it defines the contours of the group within which the contract is taking place. Finally, due to the fact that health is a typically universal value and being a primary good it is something which should be distributed justly, solidarity seems not to have any central role in bioethics.